Relationship Between Adequacy of Protein, Iron, Vitamin C, and The Incidence of Anemia in Adolescent Girls Aged 16-18 Years - Dian Ferdiyanto; Alifianti Muharramah; Dera Elva Junita; Desti Ambar Wati (Jurnal Gizi Prima (Prime Nutrition Journal), 2024)
Background: Anemia is a condition with a red blood cell count of less than <12 mg/dl. Factors that cause the high incidence of anemia in adolescents include low intake of animal and vegetable protein, iron, vitamin C, and bleeding due to prolonged menstruation.Research Methods: This study aimed to determine the relationship between adequate protein, iron, and vitamin C levels and the incidence of anemia in young women aged 16-18 years at SMA Negeri 1 Jati Agung. The research design used in this research is quantitative, utilizing a cross-sectional method. The subjects in this research were 66 female respondents from SMA Negeri 1 Jati Agung.Research Result: Base The results of the analysis using the Fisher test showed that there was no relationship between the level of protein adequacy (p = 0.633), the level of iron adequacy (p = 0.769), and the level of vitamin C adequacy (p = 0.128).Conclusion: This research concludes that there is no relationship between adequate levels of protein, iron, and vitamin C and the incidence of anemia in young women aged 16-18 at SMA Negeri 1 Jati Agung.